The communication strategies of ideologically polarized civil society organizations on Twitter: the case of Turkey - Akboğa, Sema; Arık, Engin (Springer Nature, 2022)
We investigated how ideologically polarized civil society organizations (CSOs) in Turkey use Twitter. We analyzed tweets from 20 CSOs in Turkey for a period of 7 months by using the Information-Community-Action framework. For all types of CSOs, the number of information tweets was higher than the number of action tweets, which, in turn, was higher in number than the community tweets. Religious/ conservative and anti-government CSOs posted signifcantly more tweets than secular and pro-government CSOs, respectively. Religious/conservative and pro-government CSOs posted more information and community tweets than secular and anti-government CSOs, respectively. The number of anti-government CSOs’ action tweets was higher than that of pro-government CSOs. We, therefore, propose that the ideological stance of a CSO is a factor afecting the content of its tweets in societies where CSOs are politically polarized.
Keywords: Turkey; Civil Society Organizations; Twitter; Polarization